Decreased frequency of CD73+CD8+ T cells of HIV‐infected patients correlates with immune activation and T cell exhaustion. Issue 4 (1st October 2013) - Tóth, Ilona; Le, Anh Q.; Hartjen, Philip; Thomssen, Adriana; Matzat, Verena; Lehmann, Clara; Scheurich, Christoph; Beisel, Claudia; Busch, Philipp; Degen, Olaf; Lohse, Ansgar W.; Eiermann, Thomas; et al.
Abstract : Reduced CD73 on T cells in HIV correlates with disease progression, as well as functional CD8+ T cell defects, and is partially reversible by ART. Abstract : Recent studies indicate that murine Tregs highly express the ENTDP1, as well as the 5′‐NT and thereby, suppress Teff function by extracellular adenosine production. Furthermore, CD73 seems to play a role as costimulatory molecule for T cell differentiation. In this study, we analyzed the expression of CD73 on peripheral and lymph nodal Teffs and Tregs in a cohort of 95 HIV patients at different stages of disease, including LTNP and ECs. In contrast to murine Tregs, CD73 was only expressed on a small minority (∼10%) of peripheral Tregs. In contrast, we see high expression of CD73 on peripheral CD8 + T cells. In HIV infection, CD73 is markedly reduced on all Teffs and Tregs, regardless of the memory subtype. On CD8 + T cells, a positive correlation between CD73 expression and CD4 counts ( P =0.0003) was detected. CD73 expression on CD8 + T cells negatively correlated with HLA‐DR (<0.0001) and PD1 ( P =0.0457) expression. The lower CD73 expression on CD8 + T cells was partially reversible after initiation of ART ( P =0.0016). Functionally, we observed that CD8 + CD73 + T cells produce more IL‐2 upon HIV‐specific and unspecific stimulation than their CD73 − counterparts and show a higher proliferative capacity. These data indicate that down‐regulation of CD73 on CD8 + T cells correlates with immune activation and leads to functional deficits in HIV infection.